Introduction to relational database design - Miles, Timothy J.; Safari eBooks ([S.l.] : CompuWorks, 2013)
"This course familiarizes the student with techniques to properly create and normalize a relational database. This single course can help prevent the new database developer from creating mistakes that add hours and days to a development project."--Resource description page.
Title from title screen.
Date of publication from resource description page (viewed May 29, 2013).
Presenter, Timothy J. Miles.
Keywords: Database design; Relational databases -- Design; Electronic books